2005
DOI: 10.1021/ja050810g
|View full text |Cite
|
Sign up to set email alerts
|

Zooxanthellamide Cs:  Vasoconstrictive Polyhydroxylated Macrolides with the Largest Lactone Ring Size from a Marine Dinoflagellate of Symbiodinium sp.

Abstract: Zooxanthellamide Cs (ZAD-Cs), C(128)H(220)N(2)O(53)S(2) (ca. 2.7 kDa), was obtained from a cultured marine dinoflagellate of the genus Symbiodinium as an inseparable isomeric mixture of polyhydroxylated 61- to 66-membered macrolides. The chemical structures of the components were clarified by detailed 2D NMR analysis to be the macrolactonized analogues of zooxanthellamide A (ZAD-A), which had been previously isolated from the same microalgae. Chemical lability of ZAD-Cs suggests that ZAD-A is an artifact deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…Future studies will explore this tool further, perhaps enabling higher levels of selectivity favoring large macrocycles. In this vein, the existence of large macrocyclic natural products is notable (61,62) as is the dearth of methods that provide rapid access to this size regime.…”
Section: Resultsmentioning
confidence: 99%
“…Future studies will explore this tool further, perhaps enabling higher levels of selectivity favoring large macrocycles. In this vein, the existence of large macrocyclic natural products is notable (61,62) as is the dearth of methods that provide rapid access to this size regime.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that zooxanthellae of the genus Symdiodinium, which live in symbiosis with the hydrocorals, produce large polyhydroxylated secondary metabolites, namely, zooxanthellatoxins Nakamura et al, 1993) and zooxanthellamides (Onodera et al, 2004;Onodera et al, 2005;Fukatsu et al, 2007) that are of interest due to their characteristic structure and potent vasoconstrictor activity. Recently, we found indirect evidence that the hydrocorals, not the symbiotic zooxanthellae, are the source of the vasoactive compounds present in the M. complanata aqueous extract, since we demonstrated that the extract prepared from bleached specimens displayed concentration-dependent vasoconstrictor effects that were not significantly different from those induced by the extract obtained from the control specimens .…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] In previous studies, we examined a different strain (HA3-5) of Symbiodinium and discovered another class of large polyols, zooxanthellamides (ZADs), which are distinguishable from the zooxanthellatoxins by three substructures connected via amide functionalities. [6][7][8] Zooxanthellamide C's (ZAD-C's), an isomeric mixture, contain the components with the largest lactone ring size as natural products and have higher vasoconstrictive activity than the zooxanthellatoxins. 8 A further search for the Symbiodinium metabolites using the strain JCUCS-1 resulted in the isolation of the third type of polyols named zooxanthellamide D (ZAD-D, 1), which consists of two substructures connected via an amide group.…”
mentioning
confidence: 99%
“…[6][7][8] Zooxanthellamide C's (ZAD-C's), an isomeric mixture, contain the components with the largest lactone ring size as natural products and have higher vasoconstrictive activity than the zooxanthellatoxins. 8 A further search for the Symbiodinium metabolites using the strain JCUCS-1 resulted in the isolation of the third type of polyols named zooxanthellamide D (ZAD-D, 1), which consists of two substructures connected via an amide group. We report herein the isolation, structure elucidation, and biological activity of this new metabolite.…”
mentioning
confidence: 99%